Label-free virus identification and characterization using electrochemical impedance spectroscopy - Poenar, Daniel P. (2014)
We demonstrate here the application of electrochemical impedance spectroscopy (EIS) in microfluidic devices for label-free virus identification by means of their specific “signature” and also investigate its feasibility for titer quantitation using two basic approaches. The first one is a method based on identifying so-called “resonance” frequencies manifesting in our microdevices and monitoring their variation as a function of the virus concentration, whereas the second one relies on measuring the relative impedance variation at these “resonance” frequencies. Best results have been obtained for the highest “resonance” frequency (∼80 MHz), which we attribute to be due to both the structure of the microdevice and the extremely small size of the viruses that make their effect significant only at such frequencies. This is a simpler method of determining virus concentration in diluted solutions of purified viruses than the well-established traditional plaque assay titer estimation method, and—since it is based on frequency measurement—could potentially be more accurate.